Social skills, coping, resilience and problem-solving in psychology university students - De Almeida Santos, Zeimara (2018)
This work aimed to identify the relationship between Resilience, Coping, Social Skills and Problem-Solving, and compare said constructs between psychology students and students from other areas of human sciences. Eight hundred sixteen (816) university students from public and private institutions in the state of Rio de Janeiro whose age ranged from 17 to 44 years participated in this study. The research instruments were: Social Skills Inventory Scale, Problem-Focused Coping Scale, Resilience Scale for Adults, and Problem-Solving Skills Scale. The results showed differences between the groups of students regarding social skills deficits, and a positive correlation between the Problem-Focused Coping Scale and the Problem-Solving Skills Scale. This data contributes to the initiative of adjusting the educational program for the purpose of developing the social interaction skills involved and required in the training of future psychologists.